Adaption of the passive house concept in northern Sweden : a case study of performance - Danielski, Itai; Svensson, Michelle; Fröling, Morgan (Mittuniversitetet, Avdelningen för ekoteknik och hållbart byggande, 2013)
This study analyzes the performance of a case study of low energy house built in Östersund (lat.63°N), Sweden. The building is a semi detached house for two families, with each apartment having afloor space of 160 m2 divided on two floors. The building was constructed during 2010 according tothe Swedish passive house principles with design that meet the requirements for Swedish passivehouses as defined by the Forum for energy efficiency buildings (FEBY) and the Swedish center forzero energy houses (SCNH). The house is connected to the district heating network, which is the mainheat source for domestic water heating, floor heating in the bathroom and water based pre‐heatercoil in the ventilation system. Additionally, a wood stove is installed in the living room for thermalcomfort and convenience of the residents. The two identical residential units in the building wereinhabited in the end of 2010 by families with different characteristics; a family with two youngchildren in one unit and a middle aged couple in the other.A one year energy measurement campaign started in May 2012 for both of the residential units. Themeasurements started after a period of adjustments of the building energy system and include spaceand domestic water heating (separate measurements), household electricity, the amount of fuelwood used in the stove, and indoor thermal conditions. The results show that it is possible to buildpassive houses in the Northern regions of Sweden. The specific final energy demand of the casestudy was 23% lower than the Swedish FEBY‐requirements. Differences were found between themonitored and calculated specific final energy demand. These differences depend to a large extanton the occupants’ behavior and household characteristics. The final energy demand for heating anddomestic water heating found to vary significantly between the two households. HUP